Occupational Situation of the Rural Farming and Landless Population in Poland in 2002-2017 - Włodzimierz Kołodziejczak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The Polish rural population is highly differentiated in terms of occupational situation, mainly because of the rural population’s involvement in individual farming. The purpose of this paper is to investigate the occupational situation of the rural farming and landless population in 2002, 2016 and 2017 in the context of non-farming job opportunities and unemployment risks. The study consists of two parts; the first one analyses the changes to the occupational situation of the rural population in the labour market; the second one identifies the risk of unemployment in selected groups of rural population. Aggregated weighted data and non-aggregated, non-published non-weighted BAEL (Polish LFS) data was used as source material. The study period witnessed a considerable improvement of the rural population’s occupational situation. However, if there is a slowdown in economic growth, the occupational situation of the rural population may deteriorate. In the short and medium term, people involved in individual farming and landless woman, i.e. the group where the real unemployment rate is much lower than equilibrium unemployment, will be particularly severely affected. In the longer term, the adverse impact of business cycles may also deteriorate the situation of landless men if their equilibrium unemployment level “follows” the real unemployment rate.